Happy Numbers in China and Japan - T. M. Gurevich; A. A. Voytsekhovich (Концепт: философия, религия, культура, 2020)
The paper outlines the functioning of cultural practices concerning numbers in Chinese and Japanese mundanity. The formation and use of such symbolic non-mathematical meaning of numbers is a distinctive aspect of linguistic, cultural and axiological systems in the countries of the Far East. The topic seems to be of particular interest due to high attention drawn by number-containing words and idioms in Chinese and Japanese linguistic studies in combination with cultural studies. Such an analysis seeks to develop the approaches to clarifying nation-specific mental representations and cultural aspects of using numeral vocabulary. Non-mathematical meaning of numeral vocabulary should be considered in a differentiated manner depending on factors that shape particular meanings. Religious and cosmogonic mythology as well as oriental philosophy serves as major origins of number-related meanings. Graphic interpretations also produce new associated meanings. The paper mostly delves into the effects of how the phonetics of number-containing words influences their meaning. Homonymy and homophony that are typical of the Chinese language considerably facilitate the process of mounting additional meanings. The axiological and cultural perspective embraces numbers as classifying factors that can be used to stratify the objects. The study of non-traditional meanings in number vocabulary not only allows to reveal the link between culture and language but highlights how cognitive processes operate in linguistics.